When it snowed that night - Farber, Norma; Mathers, Petra (New York, NY : HarperCollins, 1993)
A collection of nativity poems featuring animals who travel from afar to be at the manger of baby Jesus and protect him from the snow.
"A Laura Geringer book."
Keywords: Jesus Christ; Jesus Christ; Children's poetry, American; Animals; Animals; American poetry